Selección preliminar de plantas de arroz con resistencia vertical A pyricularia oryzae Cav. por inducción de mutaciones (ING) - Cruz, A; Orozco, R.; Madriz, J.; Salazar, R.; Brenes, A. (Uniciencia, 1992)
Seeds of rice Oryza sativa L. cv. CR-1113 susceptible to blast disease Pyricularia oryzae Cav. Were subjected to gamma radiation with 60Co using doses of 15 and 20 krads to obtain and select mutant plants with vertical resistance to blast. A total of 80.000 rice plants per treatment were individually evaluated in the second mutant generation (M2) at tillering and panicle emergence. Vertical resistance was observed in 47 and 8 plants from the 15 and 20 krads treatments respectively.